Model Penanaman Nilai Dan Karakter Pada Masyarakat : Kajian Systematic Literature Review (Slr) Pada Institusi Pemerintah, Institusi Sosial, Dan Ruang Publik - Dede Supriyatna; Cece Nurhikmah (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
Instilling values and character in society has become a strategic issue amidst increasingly complex developments in globalization, digitalization, and social change. Various social institutions play a crucial role in shaping societal character, through policies, organizational culture, and social interactions in public spaces. This study aims to identify models of value and character instillation applied in government institutions, social institutions, and public spaces based on a review of scientific literature. The study employed a qualitative method with a Systematic Literature Review (SLR) approach. Data were obtained from national and international scientific articles published between 2019 and 2025 through the Google Scholar, Scopus, and SINTA databases. The research stages included article identification, screening, eligibility, and thematic analysis. The results indicate four main models for instilling character values in society: (1) the social habituation model, (2) the institutional role model, (3) the participatory-communitarian model, and (4) the digital-cultural model. Government institutions tend to use a regulatory and bureaucratic role model approach, while social institutions emphasize strengthening collective culture and community participation. Public spaces serve as a strategic medium for internalizing values through social symbols, moral campaigns, and cultural activities. This study concludes that the success of instilling character values is greatly influenced by synergy between institutions, consistent social culture, and active community involvement.